ANALISIS KEBERADAAN KEPULAUAN SERIBU TERHADAP BATAS PENGELOLAAN LAUT PROVINSI DKI JAKARTA - Fauzi Janu Amarrohman; Moehammad Awaluddin; Bambang Darmo Yuwono; Aisyah Arifin (Elipsoida : Jurnal Geodesi dan Geomatika, 2020)
Province of Special Capital Region (DKI) Jakarta is one of the provinces in Indonesia which has a sea area larger than its land area. Based on this, according to Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government, the Province of DKI Jakarta can be called a province with an archipelago characteristic. The province of the archipelago has the authority to manage natural resources at sea and is assigned to carry out the authority of the central government in the marine sector based on the principle of co-administration. Determination of the management of the sea area in an island region characterized by the provisions of UNCLOS 1982. In this case the affirmation of an island territory using three reference references, namely with the coastline as a normal base line, with a straight base line, and with reference to the group of islands as baselines of the islands. The data used in this study uses the Peta Rupa Bumi Indonesia and Landsat 8 Image data acquisition in 2019. From the two data, the boundaries of the management area of the sea area are carried out digitally. In order to obtain the area of marine management of the DKI Jakarta region which is characterized by islands with the Thousand Islands and the area of sea management if the Province of DKI Jakarta is a province that is not characterized by islands. The total area of sea management in the Province of DKI Jakarta is not characterized by an archipelago is 587,453,346 Ha, whereas if the determination of the sea area management area of DKI Jakarta Province is characterized by an archipelago, the area is 587,457,404 Ha.